MEAN NUSSELT NUMBER CORRELATION FOR TISE HEATSINK THERMAL DESIGN - Sato, A. I.; Altemani, C. A. C.; Scalon, V. L. (Revista de Engenharia Térmica, 2020)
This work was developed from a review of the technical literature for the thermal design of parallel plates heat sinks with uniform cross section cooled by airflow with the TISE (Top Inlet Side Exit) configuration. Due to an observed lack of agreement of the literature correlations among themselves and also with the available experimental results, numerical simulations were then performed to evaluate the forced convective heat transfer in the channels of these heat sinks with the TISE configuration. The simulations encompassed a range of heatsink airflow rates, considering distinct channel sizes and also the effect of a partial opening for the airflow entrance at the heat sink top. The obtained numerical results were employed to evaluate the average convective heat transfer coefficient inside the heatsink’s channels, based on the flow mixed mean temperature. A new empirical correlation was then proposed for the average Nusselt number as a function of the airflow Reynolds number and three dimensionless channel geometric parameters. The new correlation was compared with available experimental data.